STUDY OF A NEW CESTODE PESUDOADENOSCOLEX FOSSILIS N.G., N.SP. FROM FRESHWATER CATFISH, HETEROPNEUSTES FOSSILIS (BL.) - MATHUR, NOOPUR; SRIVASTAV, A.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
A NEW CESTODE PESUDOADENOSCOLEX FOSSILIS N.G., N.SP. IS DESCRIBED FROM THE FRESHWATER CATFISH HETEROPNEUSTER FOSSILIS (Bloch.)